Correction to: Somatic mutations in neurons during aging and neurodegeneration - Verheijen, Bert M.; Vermulst, Marc; van Leeuwen, Fred W. (Acta neuropathologica, 2020)
In the original article, the panels "Brain organoids" and "Transgenics" were included in Fig. 5 without permission.In the original article, the panels "Brain organoids" and "Transgenics" were included in Fig. 5 without permission.